2012
DOI: 10.1021/ie300311a
|View full text |Cite
|
Sign up to set email alerts
|

Permeability, Viscoelasticity, and Flammability Performances and Their Relationship to Polymer Nanocomposites

Abstract: Despite abundant studies on gas barrier, viscoelastic, and flammability properties of polymer nanocomposites, comprehensive understandings of these performances and their relationships are still lacking. We herein attempt to gain deep insights into the performances by creating several polymer nanocomposites by incorporating three types of nanoparticles, nanoclay (Clay), carbon nanotubes (CNTs), and reduced graphene nanoplates (RGO), into polypropylene (PP). The oxygen permeability, viscoelasticity, and flammab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
58
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 39 publications
7
58
0
Order By: Relevance
“…The plasticizing effect of the nanographene leads to a reduction of relaxation time, further viscous motions, and declining elastic modulus [36,40,41] as is represented well in the modulus studied earlier.…”
Section: Relaxation Time Spectrasupporting
confidence: 70%
See 1 more Smart Citation
“…The plasticizing effect of the nanographene leads to a reduction of relaxation time, further viscous motions, and declining elastic modulus [36,40,41] as is represented well in the modulus studied earlier.…”
Section: Relaxation Time Spectrasupporting
confidence: 70%
“…As discussed earlier, shifting of H (s) to the lower level could be related to dispersion of filler and also to the lower extent of trans-reactions in the blends nanocomposites via the presence of graphene [5,40]. The plasticizing effect of the nanographene leads to a reduction of relaxation time, further viscous motions, and declining elastic modulus [36,40,41] as is represented well in the modulus studied earlier.…”
Section: Relaxation Time Spectrasupporting
confidence: 55%
“…It was also found that barrier to gas properties of the polymer composites can be enhanced (i.e. the values of the permeability to gas coefficient reduce as percentage of fiber contents increases) as documented in the literature [17][18][19][20][21][22][23][24][25][26][27] . One important key factor that enhances mechanical properties of the polymer is the aspect ratio of the fillers (i.e.…”
mentioning
confidence: 92%
“…Chopra et al 26 stated that 14% maleic anhydride in styrene-co-maleic anhydride provided higher miscibility over other compositions. Song et al 27 pointed out that graphene-based nanocomposite displayed higher storage modulus and complex viscosity as compared to nanoclay and CNT's. Ray and co-workers 28 reported that PLA/C18 MMT clay nanocomposites exhibited increased material properties in both solid state and melt state as compared to neat polymer.…”
Section: Introductionmentioning
confidence: 99%